Pituitary function after transsphenoidal surgery including measurement of basal morning cortisol as predictor of adrenal insufficiency. Issue 7 (14th July 2021) - Staby, Ida; Krogh, Jesper; Klose, Marianne; Baekdal, Jonas; Feldt-Rasmussen, Ulla; Poulsgaard, Lars; Springborg, Jacob Bertram; Andreassen, Mikkel
Abstract : Introduction: Patients with pituitary adenomas undergoing transsphenoidal surgery require pre- and post-surgery examination of pituitary hormones. There is currently no consensus on how to evaluate the adrenal axis post-surgery. The aims of this study were to investigate factors that may predict postoperative adrenal insufficiency (AI) and to investigate the overall effect of transsphenoidal surgery on pituitary function. Methods: One hundred and forty-three consecutive patients who had undergone transsphenoidal surgery for pituitary adenomas were included. Data on tumour size, pituitary function pre-surgery, plasma basal cortisol measured within 48 h post-surgery and pituitary function 6 months post-surgery were collected. Patients with AI prior to surgery, perioperative glucocorticoid treatment, Cushing's disease and no re-evaluation after 1 month were excluded ( n = 93) in the basal cortisol analysis. Results: Low plasma basal cortisol post-surgery, tumour size and previous pituitary surgery were predictors of AI (all P < 0.05). A basal cortisol cut-off concentration of 300 nmol/L predicted AI 6 months post-surgery with sensitivity and negative predictive value of 100%, specificity of 81% and positive predictive value of 25%. New gonadal, thyroid and adrenal axis insufficiencies accounted for 2, 10 and 10%, respectively. The corresponding recovery rates were 17, 7 and 24%, respectively Conclusion: Transsphenoidal surgery had an overall beneficial effect on pituitary endocrine function. Low basal plasma cortisol measured within 48 h after surgery, tumour size and previous surgery were identified as risk factors for AI. Measurement of basal cortisol post-surgery may help to identify patients at risk of developing AI.